Intensive Management Strategies to Close Wheat Yield Gaps in Central Kansas - B. R. Jaenisch; R. Lollato (Kansas Agricultural Experiment Station Research Reports, 2017)
Winter wheat is the most widely sown crop in Kansas, and yields had not surpassed 50 bushels per acre until 2015-16, when average state wheat yield was 57 bushels per acre. However, recent estimates of the long-term winter wheat yield potential in central Kansas indicate that it lies around 75 bushels per acre. A particular crop’s yield gap in a given region is determined by the difference between potential and actual yields. The long-term yield gap in Kansas is approximately 45 bushels per acre, which corresponds to more than 50% of the yield potential. Yield gaps have the potential to be economically reduced to approximately 30%. The two possible ways to reduce yield gaps are through improved agronomic management or increasing yield potential through improved genetics. Our hypothesis is that improved management can largely contribute to closing wheat yield gaps in central Kansas. Our objectives were to quantify the partial contribution of different management strategies toward closing the wheat yield gap in central Kansas, including fertilization, plant population density, fungicide, and growth regulator applications, all individually or in combination.
Keywords: Wheat; intensive management; yield gap; fungicide